Identification of IncA Plasmid, Harboring blaVIM-1 Gene, in S. enterica Goldcoast ST358 and C. freundii ST62 Isolated in a Hospitalized Patient - Alessandra Piccirilli; Sascia Di Marcantonio; Venera Costantino; Omar Simonetti; Marina Busetti; Roberto Luzzati; Luigi Principe; Marco Di Domenico; Antonio Rinaldi; Cesare Cammà; Mariagrazia Perilli (MDPI AG, 2023)
In the present study, we analyzed the genome of two S. enterica strains TS1 and TS2 from stool and blood cultures, respectively, and one strain of C. freundii TS3, isolated from a single hospitalized patient with acute myeloid leukemia. The S. enterica Goldcoast ST358 (O:8 (C2-C3) serogroup), sequenced by the MiSeq Illumina system, showed the presence of β-lactamase genes (blaVIM-1, blaSHV-12 and blaOXA-10), aadA1, ant(2")-Ia, aac(6')-Iaa, aac(6')-Ib3, aac(6')-Ib-cr, qnrVC6, parC(T57S), and several incompatibility plasmids. A wide variety of insertion sequences (ISs) and transposon elements were identified. In C. freundii TS3, these were the blaVIM-1, blaCMY-150, and blaSHV-12, aadA1, aac(6')-Ib3, aac(6')-Ib-cr, mph(A), sul1, dfrA14, ARR-2, qnrVC6, and qnrB38. IncA plasmid isolated from E.coli/K12 transconjugant and C. freundii exhibited a sequence identity >99.9%. The transfer of IncA plasmid was evaluated by conjugation experiments.